CVTE : the art of management and organization in the digital age - Zheng, Xiaoming; Cao, Shanshan; Zhang, Mengyi (London : Tsinghua University School of Economics and Management, 2020)
Before CVTE becomes a listed company, people rarely know its idiosyncratic management structure and process. None of the founders has ever served as CEO or Chair of the company, and none has ever been a majority shareholder. They have no need to clock in or out; they are accommodated in nearby apartments provided by the company; they have free canteen facilities; their children have access to high-quality company-run education; there is an internal medical center providing services not only to the employees, but to their families too. These amenities have been provided since the company began, even in the digital age and an era in which competition in the IT industry has been fierce. The key member of the founding team, Sun Yonghui, expresses the company philosophy thus: "We are committed to helping people around us succeed in their career and live a happy life..." It is this commitment that has shaped the unique management and organization of CVTE. The key positions are filled from a shortlist of candidates following a selection process in which all CVTE employees are involved to some extent and at some point.The company's unusual approach extends into product development and business development, growth and expansion. CVTE operates an internal incubation mechanism, under which more and more new businesses have emerged or developed. After the company's listing, the senior management team came under increasing pressure to sustain rapid growth. Given the limited growth space for traditional businesses, CVTE pursued new growth by continuously incubating new businesses, which placed higher demands on human capital. However, due to the uncertainty of profitability, new businesses often struggled to attract talent-specially sales personnel-unlike traditional businesses which had secured stable markets and enjoyed steady growth. Moreover, despite substantial initial investments, new businesses struggled to be profitable in the early stages. In addition, larger investme
Originally Published InZheng, X., Cao, S., & Zhang, M. (2020). CVTE: The Art of Management and Organization in the Digital Age. 6-319-351. Beijing: Tsinghua SEM China Business Case Center.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Electronic commerce -- Case studies; Management -- Case studies